A NEW GENERALIZATION OF GEORGE & VEERAMANI-TYPE FUZZY METRIC SPACE - A. Das; D. Barman; T. Bag (Проблемы анализа)
In this article, a concept of fuzzy F -metric space, which is a generalization of George & Veeramani-type fuzzy metric space, is introduced. Concepts of convergent sequence, Cauchy sequence, completeness etc. are given, and we study some properties in such spaces. Finally, some topological results are established.